Fundamental Principles of China’s Contract Law - Liming, Wang; Chuanxi, Xu (Columbia Journal of Asian Law, 1999)
On March 15, 1999, the Contract Law of the People’s Republic of China1 was adopted by the Second Session of the Ninth National People’s Congress (NPC) and scheduled to take effect on October 1, 1999. The Contract Law’s promulgation constitutes not only a major development of China’s contract law, but also an important step in China’s enactment of its much-awaited Civil Code (minfa dian).2 The Contract Law provides general provisions (entitledzongze in Chapters 1-8 in the Contract Law) for governing all types of contractual relationships,3 as well as particular provisions (entitledfenze in Chapters 9-23) for further regulation of 15 particular categories of contracts, respectively.’ As the statute that deals specifically with contracts, the Contract Law can be expected to play a crucial role in regulating China’s burgeoning market economy and in contributing to China’s further legal development. This Article attempts to discuss some of the fundamental guiding principles of the Contract Law. There are three major principles/policies, namely, those of freedom of contract (hetongziyou), good faith (chengxin), and the fostering of transactions (guli jiaoyi), that have been conscientiously followed by the law’s drafters5 and that have been essentially embodied in the law’s final formulation. By examining major provisions of the Contract Law that embody these three fundamental principles, respectively, we hope to elucidate the main spirit of the Contract Law as well as its general doctrinal structure. For ease of presentation and for want of space, we devote our primary attention to the general provisions (zongze), although particular provisions (fenze) are occasionally touched upon where relevant.